Analysis of Business Strategies on Msmes Coffee Promise Souls Branch East Telukjambe Karawang - Laras Ratu Khalida; Syifa Pramudita Faddila; Neni Sumarni (Institute of Computer Science (IOCS), 2022)
The current era of globalization requires business actors to be innovative and think creatively in developing their businesses so that they are not inferior to their competitors. Of the many businesses that are emerging today, one of the most popular businesses is the coffee shop business. Janji Jiwa Coffee Shop, Telukjambe east Karawang branch is a coffee shop that is currently trending among millennials. The purpose of this research is to find out and analyze the existing business strategy at Janji Jiwa Coffee Shop, Telukjambe east Karawang branch. The method used in this research is descriptive qualitative analysis method and analyze it using SWOT analysis. Sources of data used in this study are primary and secondary data, where primary data was obtained from observations and in-depth interviews related to business strategies at Janji Jiwa Coffee Shop, Telukjambe east Karawang branch to the research subject. The results of the SWOT analysis and the SWOT matrix show that Janji Jiwa Coffee Shop Telukjambe Timur Karawang is in Quadrant 1, where the company is in a very profitable situation. Coffee shops have opportunities and strengths so they can take advantage of existing opportunities. The strategy that must be applied in this condition is to support an aggressive growth policy (Growth oriented strategy). And in the IE matrix analysis, this business is included in the quadrant II business unit strategy where the business enters the growth and development stage.